Medication administration prior to cardiac arrest and during cardiopulmonary resuscitation: a comparative study on the knowledge of cardiology residents and nursing personnel working in anesthetics department, cardiology ward, coronary care unit and emergency department - Dimitrios Barouxis; Georgios Manomenidis; Agni Damianou; Athanasios Chalkias; Nikoletta Iakovidou; Theodoros Xanthos (Ene, 2019)
Introduction: Τhere is increased interest of the scientific community in assessing the level of knowledge on Cardiopulmonary Resuscitation (CPR) among health care professionals, mainly due to the high prevalence of cardiac arrest (CA). Research data demonstrate the health care professionals' lack of knowledge regarding medication used in CA and during CPR. Aim: To assess health care professionals' knowledge (residents, nurses and nurse assistants) on medication in CA and during CPR. Methods: A cross-sectional study was conducted in four big tertiary hospitals in Athens, Greece and in a large resuscitation educational center, in November and December 2016. Two hundred fifty six healthcare professionals, nursing personnel and doctors, working in various wards participated in the study. The participants completed a 14 questions research tool, assessing knowledge regarding medicine administration in CA and during CPR. Data were analyzed using statistical package SPSS 20. The statistical difference was set to p<0,005. Results: The majority of the sample was female (77,3%), with 57% of respondents having attended advanced life support training. The correlations between demographic characteristics and total score of correct answers showed statistical significance with age (p<0,05), educational level (p=0,011), years of working experience (p=0,033) and attendance of advanced life support seminar (p<0,01) with total score of correct answers. There was also statistically significance between total score of correct answers among nurses and doctors, with doctors showing higher score (p<0,05). Conclusions: Continuous education through seminars has a positive impact on health professionals' knowledge on medicines used during CA and CPR. It is necessary to standardize undergraduate healthcare professionals' education on pharmacokinetics aiming at the optimal management of the critically ill patient during CPR in clinical settings.